2019
DOI: 10.1111/jmi.12839
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopy analysis of the thermal phase transition from hydroxyapatita to β‐TCP observed in human teeth

Abstract: Summary Samples of enamel and dentin from human molar teeth were heated in air from room temperature (25°C) up to 1200°C and the phase transition from hydroxyapatite (HAP) to tricalcium phosphate (β‐TCP) was recorded. The changes produced in morphology and chemical composition in the tooth during heating were analysed by light microscopy, scanning electron microscopy (SEM), characteristic x‐ray energy dispersion spectroscopy (EDS), x‐ray diffraction (XRD), electron diffraction, transmission electron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In the present case, the phase transition occurs at 1400°C but in some reports this transition is seen in much lower temperature (700°C) at organic HAP samples (dental enamel and human bone) 27 . The presence of β‐TCP may be due to dehydration, decarbonization, and transformation of the carbonate groups (CO 3 2‐ ) in the HAP crystals 28 . Figure 3B shows the magnified XRD patterns of HAP‐1.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…In the present case, the phase transition occurs at 1400°C but in some reports this transition is seen in much lower temperature (700°C) at organic HAP samples (dental enamel and human bone) 27 . The presence of β‐TCP may be due to dehydration, decarbonization, and transformation of the carbonate groups (CO 3 2‐ ) in the HAP crystals 28 . Figure 3B shows the magnified XRD patterns of HAP‐1.…”
Section: Resultsmentioning
confidence: 55%
“…27 The presence of β-TCP may be due to dehydration, decarbonization, and transformation of the carbonate groups (CO 3 2-) in the HAP crystals. 28 Fig-…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…These peaks, which are shown by black arrows for S 8 sample (continuous: main peaks and dash: weak peaks) in Figure 2C, are in agreement with previous research. 19,[32][33][34][35] Reyes-Gasga and Becerril 35 extracted HA from human permanent molar teeth by heat treatment at different temperatures. The authors similarly found the TCP peaks at higher temperatures (1000°C and 1200°C).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have addressed the growing hydration of the samples joined with the Mg enrichment of apatites [30]. The meaningful crystallographic transformation of apatite into β-tricalcium phosphate (β-TCP) occurs under the influence of small amounts of Mg and elevated temperatures [31][32][33].…”
Section: Introductionmentioning
confidence: 99%